2016
DOI: 10.1007/s11011-016-9919-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased sensitivity of palmitoyl protein thioesterase 1-deficient neurons to chemical anoxia

Abstract: Infantile CLN1 disease, also known as infantile neuronal ceroid lipofuscinosis, is a fatal childhood neurodegenerative disorder caused by mutations in the CLN1 gene. CLN1 encodes a soluble lysosomal enzyme, palmitoyl protein thioesterase 1 (PPT1), and it is still unclear why neurons are selectively vulnerable to the loss of PPT1 enzyme activity in infantile CLN1 disease. To examine the effects of PPT1 deficiency on several well-defined neuronal signaling and cell death pathways, different toxic insults were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Acceleration of endocytosis through lipid rafts, abnormal autophagy, and mitochondrial dysfunction has been observed in cells derived from CLN1 patients. In the PPT1 −/− mouse model, PPT1 −/− neurons, compared to wild-type neurons, are more vulnerable to complex I inhibition by 1-methyl-4-phenylpyridinium (MPP), but less sensitive to complex IV inhibition by sodium azide, indicating that PPT1 deficiency causes alterations in the mitochondrial respiratory chain [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acceleration of endocytosis through lipid rafts, abnormal autophagy, and mitochondrial dysfunction has been observed in cells derived from CLN1 patients. In the PPT1 −/− mouse model, PPT1 −/− neurons, compared to wild-type neurons, are more vulnerable to complex I inhibition by 1-methyl-4-phenylpyridinium (MPP), but less sensitive to complex IV inhibition by sodium azide, indicating that PPT1 deficiency causes alterations in the mitochondrial respiratory chain [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some studies have demonstrated that PPT1 can functionally regulate mitochondrial complexes I and IV to influence mitochondrial respiratory chain activity [81]. This phenomenon is speculated to be associated with protein levels of key mitochondrial components such as ATP synthase F0 complex and cytochrome c oxidase subunits [82].…”
Section: Biological Function Of Protein Deacylasesmentioning
confidence: 99%
“…For instance, the mitochondrial ATP synthase F1 complex has been found to be a bona fide substrate of PPT1, and its depalmitoylation is indispensable for its proper localization (Annina et al, 2008). In addition, PPT1 regulates the function of complexes I and IV of the mitochondrial electron transport chain and thus influences the mitochondrial respiratory chain (Meyer et al, 2017). PPT1 also participates in the regulation of V‐ATPase function by affecting its localization to the PM and thus tunes the level of cellular autophagy (Bagh et al, 2017).…”
Section: Palmitoylation‐related Enzymesmentioning
confidence: 99%